A Dynamic Game with Interaction between Kantian Players and Nashian Players - Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper defines the concept of feedback Kant-Nash equilibrium for a discrete-time model of resource exploitation by infinitely-lived Kantian and Nashian players, where we define Kantian agents as those who act in accordance with the categorical imperative. We revisit a well-known dynamic model of the tragedy of the commons and ask what would happen if not all agents are solely motivated by self interest. We establish that even without external punishment of violation of social norms, if a sufficiently large fraction of the population consists of Kantian agents, the tragedy of the commons can be substantially mitigated.
Keywords: C71; D62; D71; 330; Kantian equilibrium; rule of behavior; categorical imperative